Proceedings of the 1st International Conference on Economics, Business, Entrepreneurship, and Finance (ICEBEF 2018) 2019
DOI: 10.2991/icebef-18.2019.149
|View full text |Cite
|
Sign up to set email alerts
|

Internet Banking Adoption Analysis in Medan and Bandung City using the Unified Theory of Use and Acceptance of Technology (UTAUT) Model with Culture as Moderator

Abstract: The number of internet users increase in Indonesia. Seeing this potential, many banks in Indonesia were intensified to promote online banking services by using internet media called the Internet banking. This study uses a model of technology acceptance UTAUT and add Hofstede culture as moderator. The study was conducted by distributing questionnaires in Medan and Bandung with a number of 305 respondents who use internet banking. The sampling technique used in this study is convenience sampling. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Thus this study supports calls to include local culture in technology integrated teaching practices (e.g. Giri et al, 2019;Min et al, 2008).…”
Section: Discussionsupporting
confidence: 80%
“…Thus this study supports calls to include local culture in technology integrated teaching practices (e.g. Giri et al, 2019;Min et al, 2008).…”
Section: Discussionsupporting
confidence: 80%
“…Behavior Intention (BI) has a positive significant effect on customer's adaptive behavior (AB) towards technological change in e-banking services. Serveral strudies agreed with this finding (Alalwan et al, 2017;Albashrawi et al, 2019;Baptista & Oliveira, 2015;Chua et al, 2016;Yogesh Dwivedi et al, 2017;Giri et al, 2019;Gupta & Arora, 2019;Im et al, 2011;Karjaluoto et al, 2019;Patil et al, 2020;Sharma et al, 2020;Venkatesh et al, 2003), while there were no findings have found negates the significance of this relationship. Thus, it can be noted that if the customer has an internal psychological tendency to adapt to the technological change in electronic banking services, this will lead to a specific action or behavior to use e-banking in the future.…”
Section: Discussionmentioning
confidence: 58%
“…For example; Al-Gahtani et al (2007) indicated from the empirical results that the SI is one of the factors that contribute to predicting the behavioral intention of customers to adapt to the use of technology. Similary, Albashrawi et al, (2019); Giri et al, (2019); ; Jung et al, (2020) ;Okonkwo, (2012); Sharma et al, (2020); Soh et al, (2020) also pointed out that SI positively contribute in predicting customer's BI to adapt with e-banking services.…”
Section: Social Influence (Si)mentioning
confidence: 91%